Geriatrics in Serbia nowadays - Mladen Davidović; Milan Ivanović (Биомедицинска истраживања, 2018)
The first hospital department for the treatment of elderly people in the world was founded by Laza Lazarević in Belgrade in 1881. The Division of Geriatrics of the Department of Internal Medicine at the City Hospital in Belgrade was founded in 1963, as the first one in the former Yugoslavia. The first regional department within the field of gerontology was founded at the Medical Faculty in Belgrade in 1995. In 1998, the first university textbook on geriatrics was published in Belgrade. Geriatrics exists as a subspecialization of internal or general medicine. In the last few decades, the subspecialization format has changed from subspecialization in gerontology, through the specialization in geriatrics, to the current format. In Serbia, the health activists in the field of geriatrics and gerontology are gathered by Gerontological Society of Serbia and are also members of Geriatric Section of the Serbian Medical Society. Health professionals, geriatricians and gerontologists, are members of the Serbian Association of Geriatricians and Gerontologist, which is a member of the European Geriatric Association. Currently, Serbia has more than 1.3 million inhabitants over 65 years of age. By 2050, it is estimated that one-third of the Serbian citizens will belong to the elderly population. The benefits each country has from the health professionals educated in the field of geriatrics are the following: better quality of life of elderly patients, reduction in mortality rate and increased life expectancy of the elderly, decrease in the percentage of rehospitalization of elderly patients, as well as reduction in health care costs.
Keywords: age; aging; Serbia; geriatrics; gerontology